Survival after cryptococcosis in Germany: A retrospective multicenter cohort study of patients diagnosed between 2004 and 2021 - Johanna Kessel; Anna-Catharina Rossaert; Tilman Lingscheid; Jan Grothe; Thomas Harrer; Christoph Wyen; Daniela Tominski; T. Bollinger; Anna Katharina Kehr; Sven Kalbitz; Christian Hoffmann; Oliver Cornely; et al. (Elsevier, 2024)
Cryptococcosis is the most prevalent fungal infection of the central nervous system worldwide. We performed a retrospective multicenter cohort study to gain insights into the epidemiology of cryptococcosis in Germany. We describe the use of diagnostic tests, clinical management and patient outcome. We included 64 patients with underlying HIV infection (55%) or other predispositions. Molecular typing by MLST documented 20 individual sequence types among 42 typed isolates. A fatal outcome was documented in 14% of patients in the first two months after diagnosis.